The Impact of Long-Term Particulate Matter with Diameter Micrometers ≤2.5 Exposure on Type 2 Diabetes Risk: A Meta-Analysis - Titik Anggraeni; Sarwoko; Herbasuki; Sri Sayekti Heni Sunaryanti (Masters Program in Public Health, 2025)
Background: The rising global prevalence of type 2 diabetes (T2D) has prompted investigations into environmental risk factors beyond traditional lifestyle causes. Air pollution, particularly fine particulate matter (PM₂.₅) has emerged as a potential contributor to diabetes. This systematic review synthesizes evidence from large scale cohort studies to evaluate the association between long term air pollution exposure and T2D risk. Subjects and Method: We analyzed prospective cohort studies (2020–2025) assessing air pollution and incident T2D, sourced from PubMed, Web of Science and EMBASE using the search terms: (